Three-dimensional ultrasonography of the breast; An adequate replacement for MRI in neoadjuvant chemotherapy tumour response evaluation? − RESPONDER trial. Issue 104 (July 2018) - van Egdom, L.S.E.; Lagendijk, M.; Heijkoop, E.H.M.; Koning, A.H.J.; van Deurzen, C.H.M.; Jager, A.; van Lankeren, W.; Koppert, L.B.
Highlights: Pilot study using ABVS in breast cancer response measurement during neoadjuvant chemotherapy. ABVS approaches MRI in tumour diameter and volume response evaluation. ABVS has a higher patient satisfaction when compared to breast MRI. ABVS is a promising alternative for breast cancer response evaluation during NAC. Abstract: Background: Accurate measurement of tumour response during and after neoadjuvant chemotherapy (NAC) is important and may influence treatment decisions in invasive breast cancer patients. Breast MRI forms the gold standard but is more burdensome, time consuming and costly. In this study response measurement was done with 3-D ultrasound by Automated Breast Volume Scanner (ABVS) and compared to breast MRI. Moreover, patient satisfaction with both techniques was compared. Methods and materials: A single-institution, prospective observational pilot study evaluating tumour response by ABVS in addition to breast MRI (standard care) was performed in 25 invasive breast cancer patients receiving NAC. Tumour response was evaluated comparing longest tumour diameters as well as tumour volumes at predefined time points using Bland-Altman analysis. Volume measurements for breast MRI were obtained using a fully immersive virtual reality system (a Barco I-Space) and V-Scope software. Same software was used to obtain ABVS volume measurements using an in-house developed desktop VR system. Inter- and intra-observer agreement was evaluated by Intraclass Correlation Coefficient (ICC). Results: Twenty-five patients were eligible for baseline measurement, 20 for a mid-NAC response evaluation, and five for a post-NAC response evaluation. MRI and ABVS showed absolute concordance in 73% of patients for the mid-NAC evaluation, with a 'good' correlation for the difference in longest diameter measurement (ICC 0.73, p < 0.01) as compared to baseline assessment. Concerning difference in volume measurement in the mid-NAC response evaluation showed a 'fair' correlation (ICC 0.52, p < 0.01) and in the post-NAC response evaluation an 'excellent' correlation (ICC 0.98, p < 0.01). 'Excellent' inter- and intra-observer agreement was found (ICC 0.88, p < 0.01) with comparable limits of agreement (LOA) for observer 1 and 2 in both diameter and volume measurement. Patient satisfaction was higher for ABVS compared to breast MRI, 93% versus 12% respectively. Conclusion: ABVS showed 'good' correlation with MRI tumour response evaluation in breast cancer patients during NAC with 'excellent' inter- and intra-observer agreement. ABVS has patients' preference over breast MRI and could be considered as alternative to breast MRI, in case results on an on-going prospective trial confirm these results (NTR6799).